A Mixed-Method Study of Pre-service Teachers’ Self-efficacy in the Indonesian Teacher Professional Education Program - Tomy Kartika Putra; Ardian Pitra Satya Purnama; Suroto Rosyd Setyanto (The Faculty of Teacher Training and Education (FKIP), Universitas Sebelas Maret, Indonesia, 2023)
In order to enhance the quality of national teacher selection in Indonesia, the government has introduced the Pre-service Teacher Professional Education Program (PTPE). This one-year program follows a four-year undergraduate degree and aims to produce highly qualified teachers. Teachers’ self-efficacy, which refers to the belief in one's ability to perform teaching tasks successfully, is essential in ensuring effective education. When pre-service teachers have a strong sense of efficacy during their education programs, they are more likely to be confident in assisting students in achieving learning goals. Accordingly, this study aimed to examine the pre-service teachers' self-efficacy level and identify the significant factors contributing to their development. The researchers employed an explanatory sequential mixed-method approach (Creswell, 2012) involving 37 pre-service teachers to achieve a comprehensive understanding. The study utilized the Teachers’ Sense of Efficacy Scale, the Sources of Self-Efficacy Inventory, and interviews as data collection instruments. The findings revealed two primary outcomes: 1) pre-service teachers exhibited an excessively high measure of self-efficacy, and 2) mastery experience, vicarious experience, verbal persuasion, and psychological arousal significantly contributed to pre-service teachers’ self-efficacy. The implications of this research extend to future investigation, the PTPE program, teacher educators, teacher tutors, and school leaders to support the development of pre-service teachers’ self-efficacy.